Transcriptome analysis reveals immune and metabolic regulation effects of Poria cocos polysaccharides on Bombyx mori larvae - Liu, Jiajie; Hong, Wanyu; Li, Mei; Xiao, Yang; Yi, Yunhong; Liu, Yi; Wu, Gongqing (Frontiers in Immunology, 2022)
Poria cocos polysaccharides (PS) have been used as Chinese traditional medicine with various pharmacological effects, including antiviral, anti-oxidative and immunomodulatory activities. Herein, Bombyx mori silkworm was used as a model animal to evaluate the immunomodulatory effects of PS via detecting the changes of innate immune parameters, and explore the underlying molecular mechanism of immunoregulatory effect of PS using Illumina HiSeq Xten platform. Our results demonstrated that hemocoel injection of PS significantly enhanced the cellular immunity of silkworm including the hemocyte phagocytosis, microaggregation and spreading ability. A total of 335 DEGs including 214 up-regulated genes and 121 down-regulated genes were identified in PS challenge group compared with PBS control. Gene annotation and enrichment analyses showed that many DEGs related to immune signal recognition, detoxification, proPO activation, carbohydrate metabolism and lipid metabolism were significantly up-regulated in the treatment group. KEGG-based GSEA analysis also revealed that the higher expressed gene sets in the PS treatment silkworm were mainly related to immune signal transduction pathways and energy metabolism. The results of qPCR further verified the reliability of our transcriptome data. In summary, a series of key genes and pathways related to immune responses and energy metabolism were identified via bioinformatics analysis. Our results suggested that PS can regulate the immunity of silkworm by enhancing the cellular immunity and modulating the expression levels of genes related to immune responses and physiological metabolism. These findings will lay a scientific foundation for the use of PS as an immunomodulator in the disease prevention in human beings or animals.